Human Resources Development And Employee Performance - Indira Basalamah; Muhammad Carda P; Andrie Firmansyah; Nizmah A. Bahasoan (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The purpose of this study is to determine the relationship between human resource development and how much influence human resource development has on employee performance. Which became the main variable in this study, namely; human resource development as an independent variable or independent variable (X). And employee performance as the dependent or dependent variable (Y). The population in this study is employee development carried out by the company every year, namely the overall HR development held in previous years before 2013. While the sample in this study is HR development carried out for 7 years, (according to the object studied). Sampling was carried out based on the consideration sample technique. Data collection methods used are documentation studies and direct observation. While the data analysis method used is the concept of human resource development and statistical methods with the help of the SPSS computer. After the data is processed, the results are as follows: there is a strong and positive relationship between human resource development and employee performance.Human Resources, Development, Performance